Keragaan, Potensi dan Kendala pada Usaha Kedai Kopi Di Jatinangor: Kasus pada Belike Coffee Shop dan Balad Coffee Works - Elly Rasmikayati; Sintia Afriyanti; Bobby Rachmat Saefudin (Ma'soem University, 2020)
The number of coffee shops in Jatinangor continues to grow, both on a small and large scale, often even meeting several coffee shops in one location close to the same scale of business with a menu list that is more or less the same. This situation triggers business competition among the actors. This condition occurred in 2 coffee shops in Jatinangor namely Belike Coffee Shop and Balad Coffee Works. This study aims to explore the performance, potential and constraints of coffee shop business in the Belike Coffee Shop and Balad Coffee Works. The research sites chosen were 2 coffee shops in Jatinangor namely Belike Coffee and Balad Coffee Works which were selected purposively because they were coffee shops with relatively the same business scale and were in the same / adjacent areas. The research design used was qualitative research. Data was collected through interviews with a number of key informants and literature studies. The results revealed that Belike Coffee Shop and Balad Coffee Works both have a number of unique potentials in terms of product, location, facilities, equipment, human resources and competition. While the constraints faced by both two coffee shops including the price of coffee raw materials that have surged will affect the selling price of coffee, noise, the absence of parking spaces for four wheels, equipment that cannot work properly and fluctuations in sales.